Cumulative burden of inflammation predicts colorectal neoplasia risk in ulcerative colitis: a large single-centre study. Issue 3 (17th November 2017) - Choi, Chang-Ho Ryan; Al Bakir, Ibrahim; Ding, Nik-Sheng (John); Lee, Gui-Han; Askari, Alan; Warusavitarne, Janindra; Moorghen, Morgan; Humphries, Adam; Ignjatovic-Wilson, Ana; Thomas-Gibson, Siwan; Saunders, Brian P; Rutter, Matthew D; et al.
Abstract : Objective: Ulcerative colitis (UC) is a dynamic disease with its severity continuously changing over time. We hypothesised that the risk of colorectal neoplasia (CRN) in UC closely follows an actuarial accumulative inflammatory burden, which is inadequately represented by current risk stratification strategies. Design: This was a retrospective single-centre study. Patients with extensive UC who were under colonoscopic surveillance between 2003 and 2012 were studied. Each surveillance episode was scored for a severity of microscopic inflammation (0=no activity; 1=mild; 2=moderate; 3=severe activity). The cumulative inflammatory burden (CIB) was defined as sum of: average score between each pair of surveillance episodes multiplied by the surveillance interval in years. Potential predictors were correlated with CRN outcome using time-dependent Cox regression. Results: A total of 987 patients were followed for a median of 13 years (IQR, 9-18), 97 (9.8%) of whom developed CRN. Multivariate analysis showed that the CIB was significantly associated with CRN development (HR, 2.1 per 10-unit increase in CIB (equivalent of 10, 5 or 3.3 years of continuous mild, moderate or severe active microscopic inflammation); 95% CI 1.4 to 3.0; P<0.001). Reflecting this, while inflammation severity based on the most recent colonoscopy alone was not significant (HR, 0.9 per-1-unit increase in severity; 95% CI 0.7 to 1.2; P=0.5), a mean severity score calculated from all colonoscopies performed in preceding 5 years was significantly associated with CRN risk (HR, 2.2 per-1-unit increase; 95% CI 1.6 to 3.1; P<0.001). Conclusion: The risk of CRN in UC is significantly associated with accumulative inflammatory burden. An accurate CRN risk stratification should involve assessment of multiple surveillance episodes to take this into account.